Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru di SD Negeri 01 Sangkaran Bhakti - Muhamad, Muhamad; Wibowo, Agus (CV. Creative Tugu Pena, 2022)
Principal leadership is an effective factor that can encourage schools to realize the school's vision and mission, goals and objectives through school programs that are implemented in a planned and gradual manner. Therefore school principals are required to have adequate abilities, both professional knowledge, instructional leadership, administrative skills, and social skills to improve school quality. In this study the approach taken was a qualitative approach, because qualitative research is research that intends to understand the phenomenon of what is experienced by research subjects, for example, behavior, perceptions, motivations, actions and so on, holistically and by means of descriptions in the form of words. words and language, in a special natural context and by utilizing various natural methods. Based on the results of this study, it can be concluded as follows: 1. The principal's strategy in improving teacher performance at SDN 1 Sangkaran Bhakti by implementing strategies includes: a. improve discipline, b. provide motivation, c. giving awards, d. open, e. kinship and f. discussion. 2. The obstacles experienced by the principal in improving teacher performance at SDN 1 Sangkaran Bhakti include: a. limited facilities, b. teacher commitment is not good, c. the teacher performs other businesses that sometimes interfere with his official duties, and d. mastery of the material. Keywords: Principal Leadership, Improving Teacher Performance, Teachers Performance